ISNAR study - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A two-year study to examine and analyze the national agricultural research systems (NARS) of 50 small countries (40 of them in the ACP group), is to be conducted by a research team from the International Service for National Agricultural Research...